2010
DOI: 10.1016/j.sleep.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative levels of excessive daytime sleepiness in common medical disorders

Abstract: Introduction Sleep restriction and sleep disorders are common causes of excessive daytime sleepiness (EDS). Medical disorders (MD) can also cause EDS, but previous studies have used non-standardized measures, selected samples, or have examined EDS in singular disorders. This study describes the relative degree of EDS associated with medical disorders to provide comparative data across a range of common medical conditions in a large unselected community-based sample. Methods Responses of 2612 individuals (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…Still, to the extent that TIB is under the control of the adolescent sleeper, extending TIB is a promising modifiable risk factor for reducing adolescent suicidality. In adults, others have documented a relationship between depression and excessive daytime sleepiness in adults even when controlling for TIB [45]. In a study of AI adults in North America, depression was independently associated with ESS scores but only 6.3% of subjects had a score of more than 10 [46] which is a much lower percentage than in our sample (34.2%).…”
Section: Discussioncontrasting
confidence: 70%
“…Still, to the extent that TIB is under the control of the adolescent sleeper, extending TIB is a promising modifiable risk factor for reducing adolescent suicidality. In adults, others have documented a relationship between depression and excessive daytime sleepiness in adults even when controlling for TIB [45]. In a study of AI adults in North America, depression was independently associated with ESS scores but only 6.3% of subjects had a score of more than 10 [46] which is a much lower percentage than in our sample (34.2%).…”
Section: Discussioncontrasting
confidence: 70%
“…Our findings are largely consistent with prior studies that reported a significant association between CPD and daytime sleepiness. For instance, Stroe et al (2010), in their study among individuals with various medical disorders, noted a nearly 50% increased risk of daytime sleepiness among individuals with a CPD (OR=1.46; 95% CI 1.16–1.83). In concordance with these findings, Theorell-Haglöw et al (2006) in Sweden found that participants with anxiety and depression had approximately 4.5 times higher odds of experiencing daytime sleepiness relative to healthy controls (OR=4.51; 95% CI 3.51–5.79).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study from Brazil found that PWE had a higher prevalence of EDS when compared with those without epilepsy [42]. Some studies have indicated that both seizures and AEDs may be causes of EDS in PWE [38], while others have found a correlation between depression or anxiety and EDS [35,43,44]. Importantly, a recent study in Thailand found that EDS was the cause of 33% of accidents occurring with Thai commercial truck drivers and was one of the major causes of traffic accidents in Thailand.…”
Section: Discussionmentioning
confidence: 99%